Deep Learning-Based English Language Learning Management: Improving Elementary Students' Listening Comprehension Skills - Fifin Arifiani Agustiany; Nandang Koswara (Papanda Publisher, 2026)
Elementary students' listening skills remain inadequate despite the critical role of listening comprehension in English language acquisition. Traditional teacher-centered approaches fail to engage students meaningfully, creating a gap between curriculum demands and classroom practices. This study examined the implementation of Deep Learning-based English language learning management in improving elementary students' listening skills. A qualitative case study design was employed at two elementary schools in West Java, Indonesia. Data were collected through interviews with teachers and principals, classroom observations, and document analysis, then analyzed using the Miles and Huberman interactive model. Deep Learning implementation through systematic planning, interactive instruction, and authentic assessment significantly improved students' listening comprehension. At SDN 214 Perumnas Cijerah, main idea identification increased from 45% to 78%, while at SDN Rancanileum improvements rose from 42% to 64%. Students demonstrated enhanced abilities in identifying main ideas, comprehending details, and interpreting contextual meaning. Unexpectedly, students developed metalinguistic awareness, spontaneously comparing English and Indonesian language structures. Supporting factors included teacher readiness and technological infrastructure, while obstacles involved resource limitations and variations in teacher competence. Deep Learning-based learning management effectively enhances elementary students' listening skills across diverse contexts. The study demonstrates that constructivist pedagogical approaches, when systematically implemented, foster active knowledge construction and holistic language development beyond intended instructional objectives.